2018
DOI: 10.1093/nar/gky162
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the base excision repair NTHL1 glycosylase causes genomic instability and early cellular hallmarks of cancer

Abstract: Base excision repair (BER), which is initiated by DNA N-glycosylase proteins, is the frontline for repairing potentially mutagenic DNA base damage. The NTHL1 glycosylase, which excises DNA base damage caused by reactive oxygen species, is thought to be a tumor suppressor. However, in addition to NTHL1 loss-of-function mutations, our analysis of cancer genomic datasets reveals that NTHL1 frequently undergoes amplification or upregulation in some cancers. Whether NTHL1 overexpression could contribute to cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 54 publications
(90 reference statements)
1
27
0
Order By: Relevance
“…Another limitation is that we failed to detect the protein expression of NTH1 by utilizing western blot due to the weak signaling. Although NTH1 mRNA expression showed positive correlation with its protein expression [55], we plan to reexamine its protein expression. It needs to be noted that we dissolved lycopene in DMSO, whereas ATRA and BC were dissolved in ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that we failed to detect the protein expression of NTH1 by utilizing western blot due to the weak signaling. Although NTH1 mRNA expression showed positive correlation with its protein expression [55], we plan to reexamine its protein expression. It needs to be noted that we dissolved lycopene in DMSO, whereas ATRA and BC were dissolved in ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…One of the duplicated genes is NTHL1. Its overexpression causes genomic instability and loss of contact inhibition of cells [39]. Another duplicated gene in chr.16p13.3 is PRKD1.…”
Section: Discussionmentioning
confidence: 99%
“…Emmanuel found that mismatch repair genes mutations in ovarian cancer can promote the growth of tumor cells to a distance and worsen the clinical physiology of patients [37]. Kristin discovered that the excision repair system was abnormally high in the early stage of many tumor cells and promotes tumor malignant progression [38]. Evan found that the process of tumor formation was diverse, but the cell cycle was a part that cannot be ignored [39].…”
Section: Discussionmentioning
confidence: 99%